PENGENDALIAN SOSIAL PERILAKU INDISIPLINER SISWA OLEH GURU DALAM PROSES PEMBELAJARAN SOSIOLOGI DI SMA - Ramadhan, Muhamad; Budjang, Gusti; Supriyadi, Supriyadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The title of this thesis is "Social Control of Students’ Indiscipline Behavior by Teachers in Learning Process of Sociology Class X in SMA Negeri 1 Boyan Tanjung Kapuas Hulu". The general problem of this research is how to social control the students’ indiscipline behavior by the teacher in the process of learning sociology in class X in SMA Negeri 1 Boyan Tanjung Kapuas Hulu Regency with sub-sub problem how social control of student indiscipline behavior through preventive and repressive action by teacher in process of learning sociology class X. This research uses descriptive method in qualitative form. The data collection tool uses observation guides, interview guides and documentation studies. The results showed (1) social control through preventive action has been done by teacher sociology. This is proven by the fact that before the teacher starts teaching, the teacher gave advice by reminding students about the importance of indisciplinary behavior in the classroom, providing oral guidance by showing the rules attached to the classroom wall and providing guidance and invitation by asking students to always behave in discipline in the learning process. Preventive action is also done on the sidelines of the learning process (2) social control through repressive actions have been done by sociology teachers. This is proven by the teacher to directly give verbal reprimand and give punishment to students who behave indiscipline in process of learning of sociology. Keywords: Social Control, Student Indiscipline Behavior